The Price of Oil - Aguilera, Roberto F.; Radetzki, Marian (Cambridge : Cambridge University Press, 2015)
Drawing on their extensive knowledge of the oil industry, Roberto F. Aguilera and Marian Radetzki provide an in-depth examination of the price of the world's most important commodity. They argue that although oil has experienced an extraordinary price increase over the past few decades, we have now reached a turning point where scarcity, uncertain supply and high prices will be replaced by abundance, undisturbed availability and suppressed price levels. They look at the potential of new global oil revolutions to bring the upward price push to an end and examine the implications of this turnaround for the world economy, as well as for politics, diplomacy, military interventions and the efforts to stabilize climate. This book will appeal to a wide readership of both academics and professionals working in the energy industry, as well as to general readers interested in the ongoing debate about oil prices.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).